Familial Essential Thrombocythemia Associated with MPL W515L Mutation in Father and JAK2 V617F Mutation in Daughter - Trifa, Adrian P.; Cucuianu, Andrei; Popp, Radu A. (Case Reports in Hematology, 2014)
Familial essential thrombocythemia features the acquisition of somatic mutations and an evolution similar to the sporadic form of the disease. Here we report two patients—father and daughter—with essential thrombocythemia who displayed a heterogeneous pattern of somatic mutations. The JAK2 V617F mutation was found in the daughter, while the father harbored the MPL W515L mutation. This case report may constitute further proof that in familial essential thrombocythemia there are other, still undefined, constitutional, inherited genetic factors predisposing to the acquisition of various somatic mutations (e.g., JAK2 V617F and MPL).